2022
DOI: 10.1186/s12964-022-00890-8
|View full text |Cite|
|
Sign up to set email alerts
|

Cholecystectomy promotes colon carcinogenesis by activating the Wnt signaling pathway by increasing the deoxycholic acid level

Abstract: Purpose Cholecystectomy (XGB) is widely recognized as a risk factor for colon cancer (CC). Continuous exposure of the colonic epithelium to deoxycholic acid (DCA) post-XGB may exert cytotoxic effects and be involved in the progression of CC. However, the functions of the XGB-induced DCA increase and the underlying mechanism remain unclear. Methods Colitis-associated CC (CAC) mouse models constructed by AOM-DSS inducement were used to confirm the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Bile acid can signal through its receptors, farnesoid X receptor (FXR) or Takeda G-protein-coupled receptor 5 (TGR5), to maintain the homeostasis of the intestinal epithelium [ 10 , 34 ]. However, excessive bile acids, especially cytotoxic DCA, have been proven to destroy intestinal barrier function [ 7 , 8 , 9 ] and promote colorectal cancer progression by inducing oxidative stress, inhibiting FXR signalling, or activating Wnt and EGFR signalling [ 29 , 35 , 36 , 37 , 38 ]. Several studies have demonstrated that DCA induces the downregulation of intestinal tight junction proteins, such as ZO-1 and occludin, and reduces the number of GCs [ 7 , 8 , 9 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bile acid can signal through its receptors, farnesoid X receptor (FXR) or Takeda G-protein-coupled receptor 5 (TGR5), to maintain the homeostasis of the intestinal epithelium [ 10 , 34 ]. However, excessive bile acids, especially cytotoxic DCA, have been proven to destroy intestinal barrier function [ 7 , 8 , 9 ] and promote colorectal cancer progression by inducing oxidative stress, inhibiting FXR signalling, or activating Wnt and EGFR signalling [ 29 , 35 , 36 , 37 , 38 ]. Several studies have demonstrated that DCA induces the downregulation of intestinal tight junction proteins, such as ZO-1 and occludin, and reduces the number of GCs [ 7 , 8 , 9 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCA reduces the expression of FXR, activates the Wnt signaling pathway, increases the levels of β-catenin and c-Myc, and promotes the proliferation and migration of colon cancer cells. The FXR agonist GW4064 reduces the proliferation of colon cancer cells by inhibiting the Wnt signaling pathway 106 . These studies suggest a relationship between DCA, FXR, and the Wnt signaling pathway.…”
Section: Intestinal Epithelial Cellsmentioning
confidence: 99%
“…Numerous experimental studies have confirmed the tumorigenic potential of bile acids, particularly the secondary bile acids DCA and lesser extent of the LCA (50)(51)(52)(53)(54)(55). It is important to note that the bile acids are usually considered as tumor promoters rather than tumor inducers, because the changed bile acid concentrations depend on exposure to carcinogenic chemicals or genetic susceptibility (56).…”
Section: Carcinogenic Effects Of Secondary Bile Acids On Colorectal C...mentioning
confidence: 99%